PENGARUH KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM TERHADAP AKHLAK SISWA - Amanina Hida Husnazaen; Muhammad Ja'far Nashir; S Sulistyowati (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
With the development of the current era and the morals of students are increasingly worrying and unsettling. Islamic education teachers are often targeted and cornered when many students violate school rules. However, with the personality competence of Islamic religious education teachers, students can imitate the attitudes and actions of their teachers. This study aims to determine the effect of the personality competence of Islamic religious education teachers on students' morals. This type of research is a quantitative study with the research subject at SD Al-Amin Cemani Sukoharjo. The independent variable (Variable X) in this study is the personality competence of Islamic religious education teachers, while the related variable (Variable Y) is student morals. The population of this study was 114 and the research sample was 34 respondents. In collecting data, researchers used an instrument in the form of a questionnaire consisting of 30 question items and distributed to respondents directly, testing the validity of the instrument using the Aikens validity test and testing its reliability using the Spearman Brown test. The scoring of the questions in the questionnaire uses a Likert scale of 1-4 to determine the level of personality competence of Islamic religious education teachers and students' morals. The results of this study indicate that the personality competence of Islamic education teachers is classified as good with a percentage of 44.1%. The results of hypothesis testing using Sig. (2-tailed) obtained a small significant value from the probability value (0.040 <0.05), the Pearson Correlation r value was obtained at 0.354 and can be said to be positive and based on the t value it is known that the calculation results are 0.339 or 0.354> 0.339, so it can be concluded that variable X affects variable Y.